Management's responsibility and audit procedures: review on verification of a company resources and problems encountered / Shaiful Bahri Mohd Idris - Mohd Idris, Shaiful Bahri (1992)
The balance sheet of a company, presents the various quantifiable economic resources continue to be held and used within the company, the owners of a company the shareholders and other interested parties would like to have a fair and reliable information brought by it. In conjunction with this, companies are regulated by the Companies Act to present a package of financial statements and to appoint auditors to audit the package.